Continuing education of hotel employees and their shared vision of the organization - Petrović, Pero; Živković, Dragan (Hotel and Tourism Management, 2017)
A learning organization (continuing education of the employees) is a concept that is becoming an increasingly widespread philosophy in all adaptable companies, from the largest transnational to the smallest ones. Employees at all levels of the hotel organisation, individually and collectively, mainly continuously, increase their capacities through learning so that their engagement results in the accomplishment of the very tasks they are responsible for. The work aims to point out that learning hotel organisations, especially in crisis conditions, progress in changes, that is in adaptability and flexibility. The changes are to be undergone with the total capacity and with clear goals and plans. Certainly, even the well-measured changes carry risks and increased opportunities at the increasingly turbulent tourist market with constant tumultuous changes. The insufficient speed of adjustment, let alone stagnation, leads to the failure of business activities. Therefore, in the permanent learning hotel organisation, employees constantly find information sources and learn from the experiences of other participants in the tourist market, and, above all, discuss the needs of clients and customers. For this reason, the employees’ learning is facilitated in all possible ways and rewarded for it is a great satisfaction for each individual if their work is valued. In such an organization, experiments, initiatives and innovations are encouraged, and each individual’s participation is stimulated and encouraged in the hotel company. Achievements as well as errors are analysed and disclosed publicly since the sense of caring about each individual is developed and participated in the learning organization. This is because the contemporary shared vision of the learning organisation should be built on the vision of individual members of the hotel company.